2021
DOI: 10.3390/aerospace8110316
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of Distributed Control System for Gearbox-Free More Electric Turbofan Engine

Abstract: This article presents the development of the electric turbofan engine in distributed architecture with a design thrust in the range of 3 to 7.5 and from 7.5 to 30 kN for small and medium-sized unmanned aerial vehicles. The engine subsystems are considered as separate smart modules with a built-in control system, exchanging data via a digital channel with the central engine control and diagnostics unit. The key smart engine units are combined in the following subsystems: starter and turbine generators, oil pump… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This solution also makes it possible to reduce the size of the power plant as well as drag, pipeline numbers, and shaft lines, and to achieve an optimally designed system consistent for the whole operating range. The example of using a gearbox-free turbofan engine is given in the article [2], where the authors showed the layout and advantages of a distributed pump system, confirmed by experimental data.…”
Section: Introductionmentioning
confidence: 77%
“…This solution also makes it possible to reduce the size of the power plant as well as drag, pipeline numbers, and shaft lines, and to achieve an optimally designed system consistent for the whole operating range. The example of using a gearbox-free turbofan engine is given in the article [2], where the authors showed the layout and advantages of a distributed pump system, confirmed by experimental data.…”
Section: Introductionmentioning
confidence: 77%
“…It was found that the proposed controller improves the expansion of the exhaust gas to the ambient pressure for the whole operating range of the turbojet, increasing the thrust by 14%. Popov et al [7] demonstrated two designs of a more-electric turbofan in distributed architecture for small and medium-sized unmanned aerial vehicles. The pumps and guide vane actuators were electrically driven.…”
mentioning
confidence: 99%